The effect of supportive work environment and workplace diversity on employee engagement in hotel industry - Tan, Yee Wen (2022)
Diversity at workplace was studied in many contexts but it has limited studies for employee engagement in the hotel industry. The purpose of this study is to identify the effect of supportive work environment and workplace diversity on employee engagement. A total of 179 hotel employees from Kedah states were participated in this study. The collected data were analysed using the Statistical Package for Social Science (SPSS) version 26. This study found no significant relationship between supportive work environment and employee engagement whereas, workplace diversity has significant influence on workplace diversity. Thus, it is crucial for the organization to put a great emphasize on the significant roles on workplace diversity to increased employee’s engagement in hotel industry in Kedah area